1980
DOI: 10.1080/00039896.1980.10667516
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Space-Time Clustering of Lung Cancer Deaths

Abstract: One parish in Louisiana has the highest reported incidence of lung cancer in the United States. Statistically significant space-time clustering (P < 1.0) was present among lung cancer deaths (1960-1975) in residents of the urban portion of this parish. The spatial distribution of cancer deaths in the urban portion of the parish was compared to age, year of death, race, and sex matched control deaths to determine the risk of lung cancer associated with residential proximity to industry. For industries with inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Increased risks have been reported for living close to industries such as smelters, foundries, chemical industries, and others with various emissions (Lloyd, 1978;Shear et al, 1980;Gailey and Lloyd, 1983;Lloyd et al, 1985aLloyd et al, /b, 1986Gailey and Lloyd, 1986;Smith et al, 1987;Williams and Lloyd, 1988;Xu et al, 1989;Barbone et al, 1995;Zaridze et al, 1995;Ko et al, 1997;Bhopal et al, 1998;Petrauskaite et al, 2002). Results of these studies were inconsistent, and confidence intervals of risk estimates were mostly wide.…”
Section: Cancer Risk From Outdoor Air Pollutionmentioning
confidence: 94%
“…Increased risks have been reported for living close to industries such as smelters, foundries, chemical industries, and others with various emissions (Lloyd, 1978;Shear et al, 1980;Gailey and Lloyd, 1983;Lloyd et al, 1985aLloyd et al, /b, 1986Gailey and Lloyd, 1986;Smith et al, 1987;Williams and Lloyd, 1988;Xu et al, 1989;Barbone et al, 1995;Zaridze et al, 1995;Ko et al, 1997;Bhopal et al, 1998;Petrauskaite et al, 2002). Results of these studies were inconsistent, and confidence intervals of risk estimates were mostly wide.…”
Section: Cancer Risk From Outdoor Air Pollutionmentioning
confidence: 94%
“…Several epidemiological investigations have been performed on lung cancer in industrial areas. The studies worthy of mention are the one by Blot and Fraumeni [22], who found a higher lung cancer mortality in areas with chemical, paper and pulp and petroleum industries; the one by Axelsson and Rylander [23], who investigated the possible effects of environmental exposure to chromium due to ferro-chromium alloy industries in Sweden; the one by Shear et al [24], who analysed one parish in Louisiana which had the highest incidence of lung cancer in the United States and who found an increased risk for residents within 1.2 kilometre from industrial facilities, and the study by Matanoski et al…”
Section: Studies On Populations In Industrial Areasmentioning
confidence: 98%